EKSTRAK TUNAS BAMBU (REBUNG) DAN KOMPOS MENINGKATKAN PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis quineensis jacq)DI MAIN NURSERY - Rahmi Zulhida; Windi Rahmadi (AGRIUM: Jurnal Ilmu Pertanian, 2013)
This study aims to determine the effect of Extract Bamboo Shoots ( shoots ) and compost on growth of oil palm seedlings in the Main Nursery . Experiments conducted at the Faculty of Agricultural Land Muhammadiyah University of North Sumatra , on January to May 2012 . The design used a randomized block design ( Randoimized Block Design ) factorial with three replications . Consists of two factors studied , bamboo shoots extract factor 0 cc / l of water plot ( B0 ) , 30 cc / l of water plot ( B1 ) , and 50 cc / l of water plot ( B2 ) , and compost factor 0.9 kg / plot ( K1 ) , 1.8 kg / plot ( K2 ) , and 3.6 kg / plot ( K3 ) . The parameters measured are higher palm oil plant seeds , leaf number , stem diameter , stem fresh weight , root fresh weight , dry weight of stem and root dry weight of oil palm seedlings . The study states bamboo shoots extract showed no apparent influence on all parameters were observed , whereas treatment with compost showed a significant effect on all parameters . For the interaction effect of treatment also showed no significant effect on all parameters.Keywords: rebung, compost, palm oil sawit, main nursery